DISCOURSE CATEGORY OF “INVOLVEMENT” IN ACADEMIC DISCOURSE IN THE CONTEXT OF ITS REPRESENTATION BY GRAMMATICAL CATEGORY OF MODALITY - V.I., Sokolova (Філологічні студії, 2015)
The article deals with one aspect of the manifestation of the category of “inclusiveness” (or “engagement”, “involvement”) as a category of modality. Discourse category of “involvement” directly afects the eiciency of academic communication (including communication with the reader and the author of the textbook or manual) for its actualization directly interfaced with the category of “learning motivation”, or rather “the motivation of understanding” material that ofers the teacher to the student. Reconstructing the discourse category of involvement in its functional manifestations has been described with the help of interaction “author-reader” model through the prism of grammatical category of modality. We suggest a chart of markers that were the basis for the selection of the model. The results of the analysis and synthesis of the collected database allow us to see how diverse representations of the discourse categories can be and thus focuse the attention of the student audience. The said diversity is considered as the basis of efective adaptation of students’ educational material.